Identification of drug resistance-related virulence gene mutations in 667 clinical Mycobacterium tuberculosis isolates - Zhang, Yu; Chen, Xinchang; Wang, Shiyong; Jiang, Ning; Shao, Lingyun; Chen, Jiazhen (The Journal of Infection in Developing Countries, 2024)
Introduction: Drug-resistant tuberculosis is a severe global public health threat. Virulence factors and antibiotic resistance are generally considered to play a significant role in bacterial pathogenesis. However, the interaction between resistance and virulence in Mycobacterium tuberculosis (MTB) remains unclear. Methodology: Here, we used whole genome sequences from 667 MTB isolates from 14 countries to complete an in silico evaluation of the correlations between virulence gene mutations, drug resistance, and lineage classification. The chi-square (χ2) test was used to determine whether specific virulence gene mutations and drug resistance were related. Results: Our results showed that Mce1R_G171R and Pks15_V333A, were positively correlated with streptomycin and ethambutol resistance, respectively, and Pks15_T46I was correlated with isoniazid, rifampin, ethambutol, pyrazinamide and streptomycin resistance. We also identified an additional 24 and 40 single nucleotide polymorphisms as well as 6 and 2 insertions or deletions in various virulence genes that are likely to be associated with changes in drug susceptibility in L2 and L4, respectively. Conclusions: Taken together our data suggest that there may be some degree of co-selection between virulence and resistance factors, which may help MTB more easily adapt to new environments.